KAJIAN SENSTIVITAS PADA MANUVER ZIG-ZAG KAPAL DENGAN MENGGUNAKAN MODEL WHOLE SHIP - Irfan Mufid Ramadhan (2023)
Ship maneuverability needs to be calculated accurately to prevent sea accidents. To predict the ship's maneuverability, numerical calculations based on the hydrodynamic forces that occur on the ship can be used. The ship's maneuverability is assessed based on sea trials, one of which is the zig-zag maneuver. By analyzing the effect of each hydrodynamic derivative on the zig-zag maneuver, it can be seen which hydrodynamic derivatives can be eliminated when calculated using numerical calculations. In this study the sensitivity analysis of hydrodynamic derivatives obtained using the whole ship model will be analyzed using Monte Carlo Simulation to determine the effect of each hydrodynamic derivative on the indicators affecting the zig-zag maneuvers of the 1st overshoot and 2nd overshoot. The value of the hydrodynamic derivative varies with a standard deviation of 1% - 5%. The results of the sensitivity analysis will produce hydrodynamic derivatives which are not too influential when the ship performs zig-zag maneuvers. In this study the insensitive hydrodynamic derivatives (X_vr, Y_vvr dan N_vvv) when eliminated did not change their normal distribution compared to the original, therefore these hydrodynamic derivatives had no effect on the ship's zig-zag maneuverability.